CO2 sequestration in feldspar-rich sandstone: Coupled evolution of fluid chemistry, mineral reaction rates, and hydrogeochemical properties. (1st July 2015) - Tutolo, Benjamin M.; Luhmann, Andrew J.; Kong, Xiang-Zhao; Saar, Martin O.; Seyfried, William E.
Abstract: To investigate CO2 Capture, Utilization, and Storage (CCUS) in sandstones, we performed three 150 °C flow-through experiments on K-feldspar-rich cores from the Eau Claire formation. By characterizing fluid and solid samples from these experiments using a suite of analytical techniques, we explored the coupled evolution of fluid chemistry, mineral reaction rates, and hydrogeochemical properties during CO2 sequestration in feldspar-rich sandstone. Overall, our results confirm predictions that the heightened acidity resulting from supercritical CO2 injection into feldspar-rich sandstone will dissolve primary feldspars and precipitate secondary aluminum minerals. A core through which CO2 -rich deionized water was recycled for 52 days decreased in bulk permeability, exhibited generally low porosity associated with high surface area in post-experiment core sub-samples, and produced an Al hydroxide secondary mineral, such as boehmite. However, two samples subjected to ∼3 day single-pass experiments run with CO2 -rich, 0.94 mol/kg NaCl brines decreased in bulk permeability, showed generally elevated porosity associated with elevated surface area in post-experiment core sub-samples, and produced a phase with kaolinite-like stoichiometry. CO2 -induced metal mobilization during the experiments was relatively minor and likely related to Ca mineral dissolution. Based on the relatively rapid approach to equilibrium, the relatively slow near-equilibrium reaction rates, and the minor magnitudes of permeability changes in these experiments, we conclude that CCUS systems with projected lifetimes of several decades are geochemically feasible in the feldspar-rich sandstone end-member examined here. Additionally, the observation that K-feldspar dissolution rates calculated from our whole-rock experiments are in good agreement with literature parameterizations suggests that the latter can be utilized to model CCUS in K-feldspar-rich sandstone. Finally, by performing a number of reactive transport modeling experiments to explore processes occurring during the flow-through experiments, we have found that the overall progress of feldspar hydrolysis is negligibly affected by quartz dissolution, but significantly impacted by the rates of secondary mineral precipitation and their effect on feldspar saturation state. The observations produced here are critical to the development of models of CCUS operations, yet more work, particularly in the quantification of coupled dissolution and precipitation processes, will be required in order to produce models that can accurately predict the behavior of these systems.